The fallacy of using in-basket based measures for the validation of leadership dimensions - Harold M. Schroder (SA Journal of Industrial Psychology, 2004)
Harold M. Schroder was professor of psychology at Princeton University when he conducted most of the basic research on the High Performance Leadership Competencies. Their validation across public and private organisations was carried out by Schroder and his colleagues while he was Professor of Management at the University of South Florida. He is currently involved in organisational consultancy and research: No 10 Kings Gardens, London, NW6, 4PU, UK.